The role of cholesterol crystals and ocular crystal emboli in retinal pathology - Nicholas G. Medawar; Tim F. Dorweiler; George S. Abela; Julia V. Busik; Maria B. Grant (American Heart Journal Plus)
Cholesterol crystals (CC) can be responsible for a range of clinical syndromes in the retina from asymptomatic plaques to retinal artery occlusion with clinical trials providing evidence for the efficacy in lipid lowering therapies in preventing ocular pathology. Much of the literature has focused on CC in retinal circulation as a marker of poor systemic health and have attempted to use them to categorize risk of mortality and stroke. More recently cholesterol accumulation and CC formation have been linked to development of diabetic retinopathy with CC formation in the retina due to aberrant retinal cholesterol homeostasis and not simply systemic dyslipidemia.